Riding the tiger - Burton, Geoff ([S.l.] : Australian Film Finance, 1992)
A documentary program on Indonesian social and political conditions, past and present
part 1. Kings and coolies - part 2. Freedom or death - part 3. The New Order
Copy available in DVD format
Narrator Paul Barry
Keywords: Indonesia -- Social conditions; Indonesia -- Politics and government; Documentaries and factual films and video